PENGGUNAAN MEDIA ELEKTRONIK DALAM PEMBELAJARAN DARING IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Olvin Novella; Erman Erman (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This research aimed to determine the improvement of student learning outcomes through online learning electronic media. This was a pre-experimental with one group pretest-posttest design. Data collected using written tests and response questionnaires. The learning outcomes data were analyzed using the Wilcoxon test and calculated the N-Gain score. The results of this study, namely: (1) there was an increase in student learning outcomes as evidenced by the average N-Gain score on high criteria; (2) Wilcoxon Signed Ranks test results show a significant difference between pretest and posttest results. Based on the results obtained, it can be concluded that the implementation of the science learning electronic media (E-PIPA) can improve student learning outcomes.